2018
DOI: 10.1111/1753-6405.12752
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and sociodemographic correlates of routine breast cancer screening practices among migrant‐Australian women

Abstract: Objective: To evaluate breast cancer screening (BCS) practice and explore the relationship between sociodemographic factors and breast awareness (BA), clinical breast examination (CBE) and mammography in migrant-Australian women.Method: Secondary analysis was performed on the pooled sample (n=1,744) from five cross-sectional studies of BCS rates among immigrant-Australian women, and the associated sociodemographic factors.Results: Only 19% of women participated in routine BA, 27.4% of women in the target group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 32 publications
0
28
0
Order By: Relevance
“…Breast cancer screening rates among some culturally and linguistically diverse groups are lower than the general population [14][15][16]. BreastScreen Victoria sought to develop and test strategies to engage Italian and Arabic speaking women using letters and phone calls in their preferred language, and compare these service innovations with usual practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer screening rates among some culturally and linguistically diverse groups are lower than the general population [14][15][16]. BreastScreen Victoria sought to develop and test strategies to engage Italian and Arabic speaking women using letters and phone calls in their preferred language, and compare these service innovations with usual practice.…”
Section: Discussionmentioning
confidence: 99%
“…Population subgroups at greater risk of not screening include women from some culturally diverse groups and those from lower socioeconomic backgrounds [13]. Generally, rates of cancer screening for migrants to Australia are slightly lower than the Australian born population [14][15][16]. There is also some evidence of a socioeconomic gradient in screening [17][18][19], and while this is not conclusive [20], studies have identified patterns of more advanced disease at diagnosis among diverse cultural or lower socioeconomic groups [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Although breast cancer screening (BCS) has been shown to improve mortality outcomes, preventive services continue to be underutilized among Asian compared with Western populations . Low screening participation has been attributed to cultural beliefs in Chinese and other minority ethnic group women .…”
Section: Introductionmentioning
confidence: 99%
“…In this study, more than half of all the participants, including both younger (69.5%) and older (53.3%) women, believed that they would not get breast cancer if they took good care of themselves. As reported in a recent study of Asian and African women living in Australia [34], this cultural factor plays a key role in shaping breast cancer beliefs and screening behaviors in women. For example, certain groups of women do not realize that they are at risk of getting the disease even though they feel healthy.…”
Section: Discussionmentioning
confidence: 99%